THE FUNCTIONAL RECOVERY OF STATIC VERTEBRAL DISORDERS CAUSED BY THE SCHEUERMANN DISEASE - OLTEANU M.; BONDOC-IONESCU D. (Editura Universitatii Transilvania din Brasov, 2019)
We supose that setting a suitable kinetotherapy program, associated with the patient's cooperation, can deliver significant results in the functional recovery of static vertebral disorders caused by the Scheuermann disease. The purpose of this study is creating a kinetic program to recover the spine considering the other curves that are correctly positioned: cervical, lombar, dorsal. In the following research I used appropriate kinetotherapy recovery methods such as: electrotherapy, hydrokinetotherapy, massage, exercise, reaching notable results. As evaluation methods I used the Schober test, the Harvard test, the articular balance. The efficency of the implemented program determined a 13 cm improvement regarding the Schober test, a 14 degrees increase of the spine flexion and a 22% imporvement in the Harvard test.